Multidimensional roles and clinical significance of GATA3 in breast cancer - Junjuan Tan; Weihan Chen; Kaiyan Song; Xiaoqian Zhu; Liwei Hong; Juju Zhou; Kai Chen; Haitong Lv (Frontiers in Cell and Developmental Biology, 2026)
Background GATA-binding protein 3 (GATA3) is a pivotal transcriptional regulator during mammary gland development and serves as a core biomarker in breast cancer. Although traditionally recognized for maintaining luminal differentiation, its high mutation frequency reveals a complex, dual role in tumorigenesis. Methods This review summarizes the multidimensional roles of GATA3, with an emphasis on molecular regulatory networks, clinical diagnostic applications, and significance in therapeutic response in the field of breast cancer. Results At the molecular level, GATA3 operates within a core transcriptional regulatory network, synergistically interacting with key factors like ERα and FOXA1 to govern the luminal phenotype. Clinically, GATA3 serves as a highly sensitive core biomarker for distinguishing between primary and metastatic breast cancer. Notably, emerging biomarkers like TRPS1 and SOX10 provide essential complementary value in the diagnosis of triple-negative breast cancer. High expression of GATA3 strongly correlates with a favorable prognosis and sensitivity to endocrine therapy. Conversely, downregulated GATA3 expression enhances tumor aggressiveness, increases sensitivity to certain chemotherapeutic agents such as anthracyclines, and promotes the formation of responsive “hot” microenvironment. Furthermore, although GATA3 mutations are relatively common among patients with breast cancer, their clinical and prognostic significance warrants further in-depth investigation. Conclusion As a core regulator of breast cancer cell plasticity and the tumor microenvironment, GATA3 extends far beyond its traditional role as a luminal biomarker. Elucidating its multidimensional roles and exploring its emerging therapeutic potential will continue to propel the field of breast cancer toward more sophisticated and personalized diagnostic and therapeutic paradigms.